National Emission Standards for Hazardous Air Pollutant Emissions: Hard and Decorative Chromium Electroplating and Chromium Anodizing Tanks; Group I Polymers and Resins; Marine Tank Vessel Loading Operations; Pharmaceuticals Production; The Printing and Publishing Industry; and Steel Pickling--HCl Process Facilities and Hydrochloric Acid Regeneration Plants (The Federal Register / FIND, 2010)
Proposed rule; and supplemental notice of proposed rulemaking. CFR Part: "40 CFR Part 63" RIN Number: "RIN 2060-AO91" Citation: "75 FR 65068" Document Number: "EPA-HQ-OAR-2010-0600; FRL-9203-7" Page Number: "65068" "Proposed Rules" SUMMARY: This action proposes how EPA will address the residual risk and technology reviews conducted for two national emission standards for hazardous air pollutants (NESHAP), and this action is a supplemental notice of proposed rulemaking for an October 2008 action that proposed how EPA would address the residual risk and technology reviews for four NESHAP. The six NESHAP include 16 source categories, 12 of which are the subject of residual risk and technology reviews in this package. This action proposes to modify the existing emissions standards for eight source categories in three of the six NESHAP to address certain emission sources not currently regulated under these standards. It also proposes for all six NESHAP to address provisions related to emissions during periods of startup, shutdown, and malfunction. Finally, this action proposes changes to two of the six NESHAP to correct editorial errors, make clarifications, or address issues with implementation or determining compliance.